Fatigue evaluation of a composite railway bridge based on fracture mechanics through global–local dynamic analysis. (July 2016) - Zhou, Hui; Shi, Gang; Wang, Yuanqing; Chen, Huating; De Roeck, Guido
Abstract: An enhanced fatigue assessment of critical welded details in a steel–concrete composite railway bridge was carried out by fatigue crack propagation analysis based on linear elastic fracture mechanics (LEFM). The most fatigue critical connections concerned in this study were identified by the preliminary fatigue assessment based on the S - N method in the previous research of the authors Zhou et al. (2013) . Three-dimensional crack models of the critical connections were incorporated into the global–local finite element model of the bridge. The stress intensity factor (SIF) histories of the cracks were calculated through dynamic analysis of the bridge due to the high-speed train passages, which validated the applicability and the accuracy of the empirical SIF formulas for the concerned bridge details. The fatigue crack growth curve, represented by crack size versus number of train passages, was obtained through crack propagation analysis based on the Paris law and LEFM, and fatigue propagation life was predicted for each critical connection. The proposed crack propagation analysis method provides a general and alternative approach to evaluate the fatigue life of welded details in steel bridges. Highlights: Dynamic responses of a composite bridge were accurately simulated by FE model. 3D fatigue crack models were adopted in local FE models of the critical connections. SIF histories of the cracks were obtained by global–local FE analyses of the bridge. Fatigue crack propagation analysis was performed based on the Paris law and LEFM. Fatigue propagation life was estimated for each critical connection of the bridge.